Interface of Hydrated Perfluorosulfonic Acid Electrolyte and Platinum Catalyst: Construction of a Dissipative Particle Dynamics Simulation Model. Issue 9 (23rd April 2019) - Tajima, Nobuo; Nara, Jun; Yamasaki, Takahiro; Ozawa, Taku; Nitta, Hiroya; Ohata, Kosuke; Ohno, Takahisa
Abstract : To investigate a morphological structure of hydrated perfluorosufuonic acids (PFSA) in contact with a platinum surface, we constructed a model of this interfacial system for dissipative particle dynamics (DPD) simulations. The model consists of a bead-spring model of hydrated PFSA molecules and a rigid slab of DPD particles that represents a platinum surface. We applied previously proposed soft potentials for the interactions of DPD particles of hydrated PFSA, while we constructed new ones for the interactions between those of platinum and hydrated PFSA, based on first principles calculations and all-atom classical molecular dynamics simulations. A set of DPD simulations were performed with the constructed simulation model. The calculated results suggest that hydrated PFSA tends to form layers of hydrophilic and hydrophobic components near the platinum surface.